MODEL PERSAMAAN STRUKTURAL POLA USAHATANI LAHAN GAMBUT TROPIKAL BERKELANJUTAN DI KABUPATEN BARITO KUALA - , Muhammad Husaini, Ir.,MS. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Objectives of the study are (1) to analyze sustainability of farming systems along with their indicators in tropical peatlands, (2) to analyze indicators that can be used as sustainability determinants of the farming systems, farmer capacity, availability of production factors, farmer capital condition, economic and physical condition, and farmer management capacity, (3) to formulate a structural equation model for various sustainable farming systems and to analyze impacts of farmer capacity, availability of production factors, farmer capital condition, and economic and physical condition, to the farmer management capacity, and (4) to analyze impacts of the farmer management capacity to the sustainability of various farming systems. Indicators of production, farming technology, farming income, farmer welfare, soil fertility and water quality can be used as sustainability determinants of the farming systems, as all indicators are grown up and all the farming systems are continuously executed by farmers. Almost all indicators of exogenous and endogenous variables of various farming system can be confirmed and significantly contributed. Model-4 has been restricted as the best structural equation model, such that sustainability of the farming system can be assessed by variables used in the model. Sustainability of the farming systems of paddy-paddy and paddy-coconut are mostly determined by economic environmental condition that is contributed mainly by market structures and product prices. While the farming system of paddy-citrus is significantly determined by the capital farmer condition, which is composed and contributed dominantly by sources of the capital and proportion of the farmer capital. The sustainability of various farming systems is significantly determined by the farmer management capacity which is contributed mainly by planning and execution of farming